Human dignity and fundamental rights - García Toma, Víctor (2019)
In the present article, the autor develops the concept of human dignity as a base and structure of fundamental rights. For this purpose, the basic rights of human person, its structure and effectiveness will be explained. Likewise, the essential content and the iusphilosophical importance of fundamental rights will be explained. Finally, the author will develop the importance of the institutional guarantees that these hold for their application and delimitation in the legal framework.